Star trek (2011), volume 5 ebook - Johnson, Mike (Star Trek (2011), 2013)
Find out how Doctor Leonard "Bones" McCoy found himself on a shuttle to Starfleet Academy with James T. Kirk! Learn new secrets about Uhura's past and witness her first meeting with Spock! Discover what led young Montgomery Scott to devote himself to engineering. And, witness Sulu's and Chekov's first meeting at Starfleet Academy, and learn how their paths intertwined all the way to the bridge of the Enterprise! All overseen by Star Trek writer/producer Roberto Orci. Collects issues #17 - 20! Author: Mike Johnson. Illustrator: Claudia Balboni, Tim Bradstreet. © 2013 Paramount Pictures Corporation. © CBS Studios Inc.